Practical capacity of restorative justice in Imamieh jurisprudence - Ashrafi, Ahmad; Mahmoud Majidi, Seyed; Zolfaghari, Mahdi (Opción, 2019)
Restorative justice is the result of one of the developments in the attitude towards criminal justice and crime-mindedness. The purpose of this study is to describe the functional capacity of restorative justice available in Imamieh jurisprudence through descriptive-analytical method. With the introduction of the Imams and the description of the traditions, practical traditions and practices in the tradition of the Prophet and the Imams, there are significant capacities of restorative justice in Imamieh jurisprudence, which include amnesty, peace, tolerance, and Compassion, intercession, repentance, reformation of nature, and so on, that one can use all of them in settling disputes